A Comprehensive Review on L-carnitine: A Promising Nutraceutical (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
L-carnitine (LC), which is a type of quaternary amine, is an essential element for energy metabolism in mammals, plants, and specific bacteria. Originating from the amino acid methionine and lysine, it is primarily synthesized in the kidneys and liver. L-carnitine is a pharmacologically active form of carnitine that plays a vital role in energy generation and the breakdown of fatty acids via β-oxidation in metabolism. Deficiencies in organic cation transporter-2 (OCTN2) can arise due to gene mutations or in conjunction with other conditions like renal or hepatic disorders. Deficiency in carnitine regulation results in several diseases, including cardiomyopathy, cirrhosis, diabetes, endocrine disorders, malnutrition, aging, sepsis, and malnutrition. LC is known for its anti-inflammatory and antioxidant properties. Research indicates that incorporating LC into the diet can ameliorate inflammatory ailments by decreasing the presence of inflammatory agents. Supplementation with LC is particularly useful for individuals with predominant carnitine deficiencies, which can be life-threatening, as well as certain subsidiary deficiencies like organic acid disorders, muscle wasting, and weakness. Moreover, emerging evidence suggests that LC may have therapeutic benefits for various diseases, including renal diseases, liver diseases, neurodegenerative disorders, cardiovascular diseases (CVDs), cancer, diabetes, cachexia, obesity, depression, and epilepsy.